Democratic and Republic Nepal: Increased Road Connectivity at the cost of Decreased Self Reliance - Chand, Deergh Bahadur (Journal of Tikapur Multiple Campus, 2026)
Nepal’s infrastructure landscape has undergone a significant transformation following the restoration of democracy in 1990 and the establishment of a republic in 2006, particularly through the expansion of road connectivity. This study aims to critically examine the paradox of expanded road networks by assessing their contribution to national economic growth alongside rising economic dependency. Qualitative analytical approach is taken based on secondary data, policy documents, trade statistics, and existing literature, the research assesses the socioeconomic, agricultural, and environmental concerns of increased road access. The findings relate that although enhanced connectivity has boosted transportation, market access, and trade opportunities, it has concurrently faded local production structures. Inherent agriculture, traditional handicrafts, and small-scale enterprises face extreme competition from cheaper imported goods, growing Nepal’s dependence on foreign involvements such as seeds, fertilizers, machinery, and consumer products. Improved mobility has also augmented labour migration, underpinning a remittance-dependent economy. Additionally, heavy dependence on foreign aid and contractors in road development has controlled the growth of native technical capacity and long-term financial self-reliance, while inadvertent road expansion has increased environmental degradation and disaster vulnerability. The study concludes that infrastructure development without corresponding policies demoralises self-sustainability. The findings suggest the need for balanced infrastructure stratagems that assimilate road expansion with promotion of domestic industries, sustainable agriculture, environmental safeguarding, and local technological capacity enhancement to strengthen Nepal’s long-term economic freedom.